THE INFERIORITY FEELING OF ROSE DEWITT BUKATER AND ITS INFLUENCE ON HER PERSONALITY IN JAMES CAMERON'S TITANIC MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SURAHMI , SURAHMI (2007)
The problem statement of this research is how inferiority feeling has grown and powerfully influenced Rose Dewit Bukater's personality related with the various her problems, especially by Individual Psychological Approach. Therefore, the study analyzes the movie in terms of its Individual Psychological Approach. This study belongs to qualitative study. In this method, the writer uses two data sources: they are primary and secondary data sources. The primary data source and the object of the study are the movie, Titanic itself. Meanwhile, the secondary one is any books of literature related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. The result of the study shows that first, James Cameron wants to tell us that the wealth and grandeur of human is not eternal in the world only one God. While, the second is that the human who suppression, they will be right and do everything tobe free from force. In this movie, Rose Dewit Bukater becomes frustrated and inferior about suppression from her mother and her fiancee, that she just wants to get free in her life without preventing from somebody.